Characterization of the complete mitochondrial genomes of Nematodirus oiratianus and Nematodirus spathiger of small ruminants - Guang-Hui Zhao; Yan-Qing Jia; Wen-Yu Cheng; Wen Zhao; Qing-Qing Bian; Guo-Hua Liu (Parasites & Vectors, 2014)
Abstract Background Nematodirus spp. are among the most common nematodes of ruminants worldwide. N. oiratianus and N. spathiger are distributed worldwide as highly prevalent gastrointestinal nematodes, which cause emerging health problems and economic losses. Accurate identification of Nematodirus species is essential to develop effective control strategies for Nematodirus infection in ruminants. Mitochondrial DNA (mtDNA) could provide powerful genetic markers for identifying these closely related species and resolving phylogenetic relationships at different taxonomic levels. Methods In the present study, the complete mitochondrial (mt) genomes of N. oiratianus and N. spathiger from small ruminants in China were obtained using Long-range PCR and sequencing. Results The complete mt genomes of N. oiratianus and N. spathiger were 13,765 bp and 13,519 bp in length, respectively. Both mt genomes were circular and consisted of 36 genes, including 12 genes encoding proteins, 2 genes encoding rRNA, and 22 genes encoding tRNA. Phylogenetic analyses based on the concatenated amino acid sequence data of all 12 protein-coding genes by Bayesian inference (BI), Maximum likelihood (ML) and Maximum parsimony (MP) showed that the two Nematodirus species (Molineidae) were closely related to Dictyocaulidae. Conclusions The availability of the complete mtDNA sequences of N. oiratianus and N. spathiger not only provides new mtDNA sources for a better understanding of nematode mt genomics and phylogeny, but also provides novel and useful genetic markers for studying diagnosis, population genetics and molecular epidemiology of Nematodirus spp. in small ruminants.